Makna Budaya Leksikon â€œMizuâ€ yang Tercermin dalam Peribahasa Jepang dan padanannya dalam Peribahasa Sunda - Sunarni, Nani; Johana, Jonjon (Universitas Muhammadiyah Yogyakarta, 2019)
Â This study aims to describe the meaning of the culture of mizu â€˜airâ€™ in Japanese proverbs and its equivalent in Sundanese proverbs. Data used in the form of Japanese proverbs related to water as much as 11 data. Data were analyzed using ethnolinguistic studies. Based on the results of data analysis, structurally are identified four types. Namely data that is structured in pairs, contradictions, poems, and comparisons. The analysis shows that mizu â€˜airâ€™ is a substance that cannot be separated from human life, including Japanese and Sundanese people. Therefore, the mizu â€˜airâ€™ lexicon has a viewpoint for Japanese society that manifests itself in its speech. The analysis results identified that mizu â€˜airâ€™ has cultural meanings that indicate the nature or character of the water symbol.Â